The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1590/s1517-83822011000400040
|View full text |Cite
|
Sign up to set email alerts
|

Mycoremediation of Congo red dye by filamentous fungi

Abstract: Azo, anthroquinone and triphenylmethane dyes are the major classes of synthetic colourants, which are difficult to degrade and have received considerable attention. Congo red, a diazo dye, is considered as a xenobiotic compound, and is recalcitrant to biodegradative processes. Nevertheless, during the last few years it has been demonstrated that several fungi, under certain environmental conditions, are able to transfer azo dyes to non toxic products using laccases. The aim of this work was to study the factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(10 citation statements)
references
References 31 publications
0
8
1
1
Order By: Relevance
“…(97%); however, the concentration of CR used in the present study (50 mg L −1 ) is higher than those reported for T. versicolor or Thelephora with 31 mg L −1 and 35 mg L −1 , respectively [57] (Table 1). In contrast, when the CR concentration was 50 mg L −1 , the removal observed for T. versicolor, 82%, for Aspergillus niger, 9%, for A. oryzae, 52%, for Penicillium chrysogenum, 10%, for Cladosporium rubrum, 10%, and Pleurotus ostreatus, 12% [58,59], were lower than that obtained in the present study. The removal percentages of CR by the dead mycelium of T. virens (94%) and T. viride (95%) are higher than those described for the mycelium of T. versicolor under three conditions: (a) autoclaved (90%), (b) acidic (49%), and (c) alkaline (42%) [58] (Table 1).…”
Section: Removal Of Cr and Mg By Fresh Biomass Of T Virens And T Viridecontrasting
confidence: 90%
“…(97%); however, the concentration of CR used in the present study (50 mg L −1 ) is higher than those reported for T. versicolor or Thelephora with 31 mg L −1 and 35 mg L −1 , respectively [57] (Table 1). In contrast, when the CR concentration was 50 mg L −1 , the removal observed for T. versicolor, 82%, for Aspergillus niger, 9%, for A. oryzae, 52%, for Penicillium chrysogenum, 10%, for Cladosporium rubrum, 10%, and Pleurotus ostreatus, 12% [58,59], were lower than that obtained in the present study. The removal percentages of CR by the dead mycelium of T. virens (94%) and T. viride (95%) are higher than those described for the mycelium of T. versicolor under three conditions: (a) autoclaved (90%), (b) acidic (49%), and (c) alkaline (42%) [58] (Table 1).…”
Section: Removal Of Cr and Mg By Fresh Biomass Of T Virens And T Viridecontrasting
confidence: 90%
“…As shown, the pH is a critical factor for MB biodegradation. It has been suggested that microbial cells are significantly affected by the pH of their immediate environment because they apparently have no mechanism for adjusting their internal pH [34]. The pH of dyes discharged in wastewater varies greatly as a result of their pH dependent nature.…”
Section: Effect Of Ph In the Removal Processmentioning
confidence: 99%
“…As opposed to adsorption, the degradation of azo dyes has been of significant interest as ideally, the dyes can be completely degraded by the microbial enzymes. Microorganisms capable of decolorizing and degrading dyes include filamentous fungi [87,88], yeasts [89,90], algae [91,92], and bacteria [93][94][95].…”
Section: Biological Treatment Of Dyesmentioning
confidence: 99%